Effectiveness and safety of COVID-19 vaccination in people with blood cancer - Copland, E; Hirst, J; Mi, E; Patone, M; Chen, D; Coupland, C; Hippisley-Cox, J (Elsevier, 2024)
Background: People with blood cancer have increased risk of severe COVID-19 outcomes and poor response to vaccination. We assessed the safety and effectiveness of COVID-19 vaccines in this vulnerable group compared to the general population. Methods: Individuals aged ≥12 years as of 1st December 2020 in the QResearch primary care database were included. We assessed adjusted COVID-19 vaccine effectiveness (aVE) against COVID-19-related hospitalisation and death in people with blood cancer using a nested matched case-control study. Using the self-controlled case series methodology, we compared the risk of 56 pre-specified adverse events within 1–28 days of a first, second or third COVID-19 vaccine dose in people with and without blood cancer. Findings: The cohort comprised 12,274,948 individuals, of whom 81,793 had blood cancer. COVID-19 vaccines were protective against COVID-19-related hospitalisation and death in people with blood cancer, although they were less effective, particularly against COVID-19-related hospitalisation, compared to the general population. In the blood cancer population, aVE against COVID-19-related hospitalisation was 64% (95% confidence interval [CI] 48%−75%) 14–41 days after a third dose, compared to 80% (95% CI 78%−81%) in the general population. Against COVID-19-related mortality, aVE was >80% in people with blood cancer 14–41 days after a second or third dose. We found no significant difference in risk of adverse events 1–28 days after any vaccine dose between people with and without blood cancer. Interpretation: Our study provides robust evidence which supports the use of COVID-19 vaccinations for people with blood cancer.